Molecular Cloning and AlphaFold Modeling of Thyrotropin (ag-TSH) From the Amazonian Fish Pirarucu (Arapaima gigas) - Freire, Renan Passos; Hernandez-Gonzalez, Jorge Enrique [UNESP]; Lima, Eliana Rosa; Suzuki, Miriam Fussae; Oliveira, João Ezequiel de; Torai, Lucas Simon; Bartolini, Paolo; Soares, Carlos Roberto Jorge (SAGE Publications, 2023)
Arapaima gigas, known as Pirarucu in Brazil, is one of the largest freshwater fish in the world. Some individuals could reach 3 m in length and weight up to 200 kg. Due to extinction risks and its economic value, the species has been a focus for preservation and reproduction studies. Thyrotropin (TSH) is a glycoprotein hormone formed by 2 subunits α and β whose main activity is related to the synthesis of thyroid hormones (THs)—T3 and T4. In this work, we present a combination of bioinformatics tools to identify Arapaima gigas βTSH (ag-βTSH), modeling its molecular structure and express the recombinant heterodimer form in mammalian cells. Using the combination of computational biology, based on genome-related information, in silico molecular cloning and modeling led to confirm results of the ag-βTSH sequence by reverse transcriptase-polymerase chain reaction (RT-PCR) and transient expression in human embryonic kidney (HEK293F) cells. Molecular cloning of ag-βTSH retrieved 146 amino acids with a signal peptide of 21 amino acid residues and 6 disulfide bonds. The sequence has a similarity to 39 fish species, ranging between 43.1% and 81.6%, whose domains are extremely conserved, such as cystine knot motif and N-glycosylation site. The Arapaima gigas thyrotropin (ag-TSH) model, solved by AlphaFold, was used in molecular dynamics simulations with Scleropages formosus receptor, providing similar values of free energy ΔGbind and ΔGPMF in comparison with Homo sapiens model. The recombinant expression in HEK293F cells reached a yield of 25 mg/L, characterized via chromatographic and physical-chemical techniques. This work shows that other Arapaima gigas proteins could be studied in a similar way, using the combination of these techniques, recovering more information from its genome and improving the reproduction and preservation of this prehistoric fish.
Keywords: AlphaFold; Arapaima gigas; in silico prediction; thyrotropin